Provision of Contraceptive Devices for School-Aged Children and Adolescents: a Comparison of Maqasid Al-Syariah and Positive Law - Andi Muh. Taqiyuddin BN; Nursarah A. Conoras; Ahmad Arief; Suprijati Sarib; Muhammad Muhammad (FASYA Press, 2025)
This study aims to examine the criticism of Maqashid al-Syariah and Positive Law against Article 103 paragraph 4 of Government Regulation No. 28 of 2024. This is a qualitative study. The research design is a literature review. The findings of this study indicate that the regulation on the provision of contraceptives for school-age children and adolescents without clearly specifying the qualifications of recipients is only applicable to those who are married. This is considered contrary to the Child Protection Law and Maqasid al-Syariah. Furthermore, the regulation on the provision of contraceptives for school-age children and adolescents is inconsistent with Article 534 of the Criminal Code, which promotes contraceptives, and Article 408 of Law No. 1 of 2023, which prohibits the promotion of contraceptives to children, with the threat of a criminal fine.